Prevalence of nasolacrimal canal obstruction and epiphora following maxillary orthognathic surgery - DERGİN, GÜHAN (CHURCHILL LIVINGSTONE, 2018)
Acquired injuries of the nasolacrimal apparatus may be the result of craniomaxillofacial surgical procedures, facial trauma, or inflammation. Injury to the nasolacrimal duct system following maxillary orthognathic surgery is rarely reported. This study evaluated the importance of early diagnosis and treatment of epiphora developing after Le Fort I surgery. The records of 83 patients who underwent maxillary orthognathic surgery over a 2-year period were reviewed. The prevalence of postoperative epiphora was 3.6% and it persisted for a mean of 32.7 days. No patient required further surgical treatment of the nasolacrimal duct obstruction. Clinicians should evaluate the lacrimal canal position and schedule close postoperative follow-up of injuries to the nasolacrimal apparatus. These may become permanent, necessitating additional surgery.
Keywords: nasolacrimal duct; orthognathic surgery; Le Fort I; epiphora; LACRIMAL DUCT OBSTRUCTION; FORT-I OSTEOTOMY; ORBITAL CELLULITIS; COMPLICATIONS; DACRYOSCINTIGRAPHY; DACRYOCYSTORHINOSTOMY; DACRYOCYSTOGRAPHY; DACRYOCYSTITIS; EXPERIENCE; ABSCESS